A Recognition Method of Soybean Leaf Diseases Based on an Improved Deep Learning Model - Yu, Miao; Ma, Xiaodan; Guan, Haiou; Liu, Meng; Zhang, Tao (Frontiers in Plant Science, 2022)
Soybean is an important oil crop and plant protein source, phenotypic traits’ detection for soybean diseases, which seriously restricts the yield and quality, is of great significance for soybean breeding, cultivation and fine management. The recognition accuracy of traditional deep learning model is not high, chemical analysis operation process of soybean diseases is time-consuming. In addition, artificial observation and experience judgment is easily affected by subjective factors and difficult to guarantee the accuracy of the objective. Thus, a rapid identification method of soybean diseases was proposed based on a new residual attention network (RANet) model. First, soybean brown leaf spot, soybean frogeye leaf spot and soybean phyllosticta leaf spot were used as research objects, OTSU algorithm was adopted to remove the background from the original image. Then, the sample dataset of soybean disease images was expanded by image enhancement technology based on the single leaf image of soybean disease. In addition, the residual attention layer (RAL) was constructed using attention mechanisms and shortcut connections, which further embedded into the residual neural network 18 (ResNet18) model. Finally, a new model of RANet for recognition of soybean diseases was established based on attention mechanism and idea of residuals. The result showed that the average recognition accuracy of soybean leaf diseases was 98.49%, and the F1- value was 98.52 with recognition time of 0.0514s, which realized an accurate, fast and efficient recognition model for soybean leaf diseases.